The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0195983
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analyses of factors related to anxiety and depression in patients with retinitis pigmentosa

Abstract: The purpose of this study is to determine the factors related to anxiety and depression in patients with retinitis pigmentosa (RP). The status of anxiety and depression was determined in RP patients with the Hospital Anxiety and Depression Scale (HADS) questionnaire which consisted of subscales for HADS-anxiety (HADS-A) and HADS-depression (HADS-D). The vision-specific quality of life (VSQOL) was assessed with the National Eye Institute Visual Function Questionnaire 25 (NEI-VFQ25). The correlations between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
(32 reference statements)
1
22
0
2
Order By: Relevance
“…This finding alone, although controversial among previous studies, has been reported in the past. [18][19][20][21][22][23][24] To further understand the implications of this difference, further analysis was completed to calculate the effect size or magnitude of this difference. This value is presented in terms of increased odds of patients with RP to have a diagnosis of anxiety by 4.9-fold, depression by 5.6-fold, and both anxiety and depression by 4.1-fold when compared with those without RP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding alone, although controversial among previous studies, has been reported in the past. [18][19][20][21][22][23][24] To further understand the implications of this difference, further analysis was completed to calculate the effect size or magnitude of this difference. This value is presented in terms of increased odds of patients with RP to have a diagnosis of anxiety by 4.9-fold, depression by 5.6-fold, and both anxiety and depression by 4.1-fold when compared with those without RP.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly because of variations in the base study populations, the presence of increased risk, variance in the reported rate, and presence of influencing patient characteristics are conflicting. [18][19][20][21][22][23][24] Similarly, investigations on the relationship between RP and anxiety have also produced conflicting reports on the association. 19,20 Although it is important to identify the presence or absence of an association between RP with anxiety and depression, the magnitude or effect size of the difference is equally significant.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al found that worse self-reported visual function assessed by Glaucoma Quality of Life-15 questionnaire (GQL-15) was consistently correlated with decreased anxiety and depression in glaucoma patients [2]. In retinitis pigmentosa patients, the degree of anxiety was signi cantly correlated with the general health and role di culties of the NEI VFQ-25 dimensions but not with any objective visual functions, such as BCVA of better-and worse-seeing eyes [19]. With regard to depression, our results were consistent with several previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Reading a book at home could be more efficiently supported by a text-to-sound or -voice application on a personal computer. Visual function impairment can cause vision-related impairment of QOL 24 , and obtaining a visual field with a view greater than 20 degrees may be useful for walking 25 . The current device that improved the visual field to almost 20 degrees would, at least in part, have a clinically relevant effect.…”
Section: Discussionmentioning
confidence: 99%